Livestock as a pathway to women’s empowerment in low- and middle-income countries: A scoping review - Baltenweck, Isabelle; Achandi, Esther L.; Bullock, Renee M.; Campbell, Zoë A.; Crane, Todd A.; Eldermire, Erin R.B.; Gichuki, Leah; Haan, Nicoline C. de; Katz, Elizabeth; Njiru, Nelly; Njuguna-Mungai, Esther; Poole, Elizabeth J.; et al. (Informa UK Limited, 2024)
Progress towards women’s empowerment (WE) and gender equality is slow and uneven across the Global South. Livestock systems support the livelihoods of one billion poor people in low- and middle-income countries (LMICs), most of whom are women. While livestock and gender research has focused on addressing gender inequalities to build a better livestock sector, there is growing evidence that livestock development can contribute to WE and gender equality. The latter is the main topic of this scoping review. A total of 99 papers, corresponding to 102 studies, were included in the analysis. Results indicate that the gender approach strongly influences the effect of livestock interventions on WE, as much as the type of livestock intervention. Gender accommodative approaches were associated with more advances in WE than gender blind approaches, but there was no significant difference in the reported negative effects, challenging the prevailing assumption that gender-accommodative approaches ‘do no harm’. Most asset transfer projects combined with extension had positive effects while those focusing on output markets negatively impacted WE. Gender accommodative approaches had negative or unclear impacts on women’s labour and workloads. Use of these findings should help guide the design of livestock projects aiming to enhance gender equality.